Announcement - The Paper Award of Tribology Online - - Masabumi Masuko (Japanese Society of Tribologists, 2011)
The Japanese Society of Tribologists is pleased to announce that the 2010 Paper Award of Tribology Online was awarded to:“Acoustic Emission Signals and Wear Phenomena on Severe-Mild Wear Transition,” by Alan Hase, Masaki Wada and Hiroshi Mishina, Vol. 3, No. 5 (2008) 298-303.and“Measurements of Impact-Induced Fracto-Emission from Soda-Lime Glass and Simultaneous Observation of the Cracking Process by High-Speed Photography, ," by Seisuke Kano, Yuji Enomoto and M. Munawar Chaudhri, Vol. 5, No. 2 (2010) 111-117.The Award Medals were presented to the authors by Prof. Shigeyuki Mori, the former President of the Japanese Society of Tribologists, at the JAST Annual Meeting on 17th May, 2011.The Paper Award of Tribology Online is given annually to the author(s), either the JAST members or non-members, of the paper(s) judged as the best paper(s) published in Tribology Online (TROL) for the previous three years. All papers that appeared in TROL for the three years are reviewed by the JAST Awards Committee.